Analisis perilaku pekerja seks komersial dalam memanfaatkan layanan kesehatan di LOKALISASI tegal panas kecemasan BERGAS Kabupaten Semarang - Sunarti, sunarti; Suratmi, Tri; Darwis, Darnialis (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2019)
ANALYSIS OF COMMERCIAL SEX WORKERS BEHAVIOR IN UTILIZING HEALTH SERVICES IN LOCALITATION DISTRICT OF SEMARANGABSTRACT Sexually transmitted infections are diseases caused by bacteria, viruses, parasites, or fungi that are transmitted from one person to another through sexual contact or relationship. Most sufferers in Indonesia are those of productive age aged 20-39 years. In Indonesia the number of cases of STIs with enforcement of diagnoses based on the syndrome approach and laboratory examination according to the highest risk group were female sex workers with a total of 8,765 cases. Commercial sex workers are at risk of contracting sexually transmitted diseases. STIs can increase the risk of contracting HIV (Human Immunodeficiency Virus) infection, making them have the opportunity to get STIs with their jobs serving many different customers. This study aims to analyze the behavior of commercial sex workers in utilizing health services in Tegal Panas Localization.The research design used was descriptive qualitative. The subjects in this study were six commercial sex workers and three key informants (Health and Pimps). The object in this study is the behavior of sex workers in utilizing health services. The methods in this study were observation, in-depth interviews and Focus Group Discussion conducted at Tegal Panas Localization using data analysis, namely content analysis and data reduction.Knowledge of sex workers such as signs of symptoms and types of STIs is still lacking, but is good enough in terms of prevention and treatment of STIs, most of them protect themselves by taking antibiotics and washing genitals with antiseptic. The use of condoms is based on agreements with customers and health services that have not been utilized by all existing commercial sex workers in Localization. Keyword          : Sex Workers, Behavior, STIs